Strategies Employed by Black Canyon Coffee Restaurant to Market Their Products - Hafez Kurniawan; Chrisjatender Chrisjatender; Syaharuddin Syaharuddin (TourEcon: International Journal of Tourism and Economic Studies, 2024)
This study explores the various strategies implemented by Black Canyon Coffee Restaurant to effectively market their products. Through a comprehensive analysis, this research examines the tactics employed by the restaurant to promote its offerings in a competitive market. Strategies such as social media engagement, experiential marketing, product diversification, and customer loyalty programs are investigated to understand their impact on brand visibility and consumer engagement. The findings shed light on the innovative approaches adopted by Black Canyon Coffee Restaurant to enhance its marketing efforts and maintain a strong presence in the industry.